Hubungan Pola Asuh Ibu Dengan Kejadian Stunting Pada Anak Usia 24 -60 Bulan di Kelurahan Teritih Wilayah Kerja Puskesmas Kalodran Kota Serang Provinsi Banten Tahun 2022 - Annisa Nurhayati Hidayat (Jurnal Anestesi, 2023)
Stunting (dwarf) is a condition where a toddler has a length or height that is less when compared to age. This condition indicates a poor nutritional status (malnutrition) over a long period of time (chronic). The purpose of this study was to find out the relationship between maternal parenting and the incidence of stunting in children aged 24-60 months in the Teritih sub-district, the working area of the Kalodran Public Health Center, Serang City, Banten Province in 2022. This research is descriptive and this research uses primary data with a measuring instrument, namely a questionnaire that has been tested as an instrument , in data analysis using the Chi Square statistical test with a sample of 14 pregnant women who have children aged 24-60 months and the researchers chose respondents with total sampling technique. Most of the results were obtained in providing food with democratic parenting as many as 9 (64.3%) and almost all respondents who were stunted were short as many as 10 (71.4%). The results of the chi square test showed P = 0.000, which means that there was a significant relationship between parenting style and the incidence of stunting and the OR value of 1.400 indicated that democratic parenting was more at risk of stunting once than authoritarian parenting in providing food or nutrition to children. It is recommended to increase knowledge and provide direct experience for researchers so that it becomes a reference material for comparing theories with stunting incidents in the community.